Potential implications of carbon dioxide removal for the sustainable development goals. (28th May 2021) - Honegger, Matthias; Michaelowa, Axel; Roy, Joyashree
ABSTRACT: As the international community's best expression of a collective vision of a desirable future, the 2015 UN Sustainable Development Goals (SDGs) present a framework against which to assess the broader impact of emerging technologies. Implications of technologies and practices for removing CO2 from the atmosphere (CDR) are not fully understood and have not yet been mapped against the full range of SDGs. CDR is widely seen as necessary to achieve the Paris Agreement's global goal of limiting warming to 1.5-2°C, yet local geographical, socio-economic, and political interdependencies are often overlooked. This review synthesizes the best available understandings of potential implications of CDR options aiming to complement emissions reductions. It seeks to identify effects on and interactions between specific social, environmental, and policy environments, in which various CDR options could be pursued. Climate change mitigation and co-benefits from CDR could significantly benefit SDGs, yet poorly designed CDR policies could also challenge SDGs. Specific CDR options could generate conflicts over land, water, biomass, or electric power resources, and exclude communities from policy benefits with negative cascading effects for a range of SDGs. In the literature, implications of CDR activities on sustainable development are derived from current pilot activities, inferred from similar practices already operational or model outputs regarding land, energy, or material requirements. Important gaps remain. We identify questions for further disciplinary and inter- or transdisciplinary work strengthening understanding of how CDR could either support or threaten the achievement of the SDGs. Key policy insights CO2 removal (CDR) appears essential for limiting warming to well below 2°C; such stabilization of global climate is a precondition for at least partially achieving the SDGs. CDR options can generate positive and negative local/regional impacts on various SDGs via physical, social, economic, and political channels. None of these options are universally 'good' or 'bad'. The scale of implementation of CDR and related impacts are highly dependent on policy design and national planning processes. More research is needed to clarify how policy design can allow CDR options to generate synergies between, and prevent harm across, multiple SDGs.